Evaluation of performance and capacity of the Spanish health system in the SARS-CoV-2 pandemic (Research, Society and Development, 2021)
Introduction: Spain was one of the countries most affected by the SARS-CoV-2 pandemic. Although Spanish public health is recognized as one of the best European health systems, the peak of cases in a short period has damaged the system mentioned above. Performance evaluation has a fundamental role in the management of health systems, presenting indicators to support short and long-term decision support for planners. Methodology: This study used documentary research from the public database of the Spanish health system and DEA to assess the efficiency of the care provided. The steps to assess the impact of SARS-CoV-2 on the efficiency of the healthcare system are described by an estimate of the efficiency of SARS-CoV-2, followed by a comparison of efficiency simulated feaseble sceneries and reductions in inlet clearances during the period demonstrating an event week by week using a baseline. Results: Coordinated actions to expand the capacity of the system can be presented, taking into account that critical entries may contradict Spain's health system. It was identified that the number of nurses was considered a critical entry. If this entry is not of adequate size, the health care system may collapse in the short term. Final considerations: The expansion policies in the health system were observed as a parsimonious model and with few contributions, since the health system uses relative numbers of ideal amounts of devices for professionals.